Glyoxalases in Urological Malignancies - Cinzia Antognelli; Vincenzo Nicola Talesa (2018)
Urological cancers include a spectrum of malignancies affecting organs of the reproductive and/or urinary systems, such as prostate, kidney, bladder, and testis. Despite improved primary prevention, detection and treatment, urological cancers are still characterized by an increasing incidence and mortality worldwide. While advances have been made towards understanding the molecular bases of these diseases, a complete understanding of the pathological mechanisms remains an unmet research goal that is essential for defining safer pharmacological therapies and prognostic factors, especially for the metastatic stage of these malignancies for which no effective therapies are currently being used. Glyoxalases, consisting of glyoxalase 1 (Glo1) and glyoxalase 2 (Glo2), are enzymes that catalyze the glutathione-dependent metabolism of cytotoxic methylglyoxal (MG), thus protecting against cellular damage and apoptosis. They are generally overexpressed in numerous cancers as a survival strategy by providing a safeguard through enhancement of MG detoxification. Increasing evidence suggests that glyoxalases, especially Glo1, play an important role in the initiation and progression of urological malignancies. In this review, we highlight the critical role of glyoxalases as regulators of tumorigenesis in the prostate through modulation of various critical signaling pathways, and provide an overview of the current knowledge on glyoxalases in bladder, kidney and testis cancers. We also discuss the promise and challenges for Glo1 inhibitors as future anti-prostate cancer (PCa) therapeutics and the potential of glyoxalases as biomarkers for PCa diagnosis.